1995
DOI: 10.1080/00206819509465438
|View full text |Cite
|
Sign up to set email alerts
|

Turbidite-Hosted Gold Deposits in the Bendigo-Ballarat and Melbourne Zones, Australia. II. Nature of Ore Fluids

Abstract: Fluids in mesothermal, turbidite-hosted, gold vein deposits in central Victoria, Australia are characterized by temperatures ranging from 180 to 310° C and salinities of less than 10 wt% NaCl equivalent. From west to east there is a general decrease in temperatures, averaging near 300° C in the western Bendigo-Ballarat Zone (BBZ), 270° C in the eastern BBZ, and 230° C in the Melbourne Zone (MZ). Pre-mineralization veins generally are lower in temperature than those hosting mineralization, whereas post-minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Reaction (6) may be responsible for the regional siderite spotting seen in many terranes. Methane has been observed in fluid inclusions in many gold deposits, including Archean deposits, and in some cases much of this is likely to be locally derived (such as in deposits situated amongst carbonaceous units; e.g., Gao and Kwak, 1995). In other localities the observation of methane requires an external source.…”
Section: Does Methane Drive Desulfidation In Rocks Adjacent To Carbonmentioning
confidence: 97%
“…Reaction (6) may be responsible for the regional siderite spotting seen in many terranes. Methane has been observed in fluid inclusions in many gold deposits, including Archean deposits, and in some cases much of this is likely to be locally derived (such as in deposits situated amongst carbonaceous units; e.g., Gao and Kwak, 1995). In other localities the observation of methane requires an external source.…”
Section: Does Methane Drive Desulfidation In Rocks Adjacent To Carbonmentioning
confidence: 97%
“…18). At Nagambie, the quartz has δ 18 O values of 20.5 to 22.9%o (Gao et al, 1995). The δ 18 O range of veins in the Walhalla-Woods Point dike swarm (after Green et al, 1982;Wilson and Golding, 1988) are shown for comparison.…”
Section: Oxygen Isotopesmentioning
confidence: 97%
“…At Maxwells, the range in δ 18 O values is only 0.7%o for laminated vein quartz (17.2) and recrystallized quartz (17.9), whereas at the New Cambrian Mine, the comparable values are 16.7 and 17.5%o. The only quartz samples with δ 18 O values outside these ranges are from stage 2 and stage 4 (19.1 and 14.8%o quartz, respectively) in the Wattle Gully mine, which pre-and post-date a fluid immiscibility event (see Gao and Kwak, 1995). However, the low δ 18 O value (14.8%o) cannot be attributed to immiscibility because: (1) phase separation of vapor H 2 O will result in the depletion of δ 18 O in the vapor and enrichment of 18 O in quartz, and (2) although CO 2 is a volatile substance that strongly partitions 18 O (Bottinga, 1968), there is little fractionation of 18 O / 16 O between CO 2 in solution and CO 2 vapor.…”
Section: Oxygen Isotopesmentioning
confidence: 99%
See 2 more Smart Citations